INVITE a virtual reality tour and user education software for the U.P. Diliman Main Library - Carandang. Tristan Joy DR.; Mallari, Florenda D. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The objectives and goals of the study were to create a virtual reality tour software featuring the UPD Main Library and provide a template of this virtual reality tour software for future application in other libraries. The software was named INVITE, which is an acronym for Interactive Virtual Tour Emulation. The name also signifies an invitation to the institution featured by the software. INVITE was developed with the versatility of featuring different types of institutions such as museums, galleries, and other places for learning. The INVITE beta prototypes were tested and evaluated by the University Librarian, the UPD Main Library section heads, several ILIS students and staff and the users of the library for feasible implementation and adaptation of the UPD Main Library.
INVITE was conceptualized, designed and created within a a period of seven (7) months using games authoring software, digital photo editors, and several 3D computer graphics software. It was tested and evaluated, upon completion of a beta prototype, using an evaluation rating sheet which was formulated based on the evaluation rating sheet by Milo (2001). The evaluation was done in order to determine the usability and acceptability of INVITE which generated 44 respondents.
Upon review of the Evaluation Rating Sheets, it can be assumed that INVITE has sufficiently achieved its objectives as an orientation and instruction program. The high ratings and positive responses were adequate enough to describe INVITE, featuring the UPD Main Library, as a suitable alternative and means of library user education. Inevitably, prior to INVITE's completion, visible errors, bugs and unimportant components were detected and taken to account during its testing and development period. These were removed by the researcher in order to optimize INVITE.
Overall, the study was able to accomplish its main objectives of creating a virtual reality tour software featuring the UPD Main Library and providing a workable template for possible application to other libraries and institutions. INVITE was found usable, acceptable and recommendable to the library users.
The high ratings that INVITE acquired among the evaluators, testers and a sample of library users may prove that INVITE is an indispensable tool for library user education. INVITE is the first application of virtual reality to the Philippine library setting and it has surpassed, based from its evaluation, interactive multimedia software programs and other methods of library user education. The final release of INVITE shall be installed in an able computer together with the OPAC computer terminals in the building's first floor lobby and be made available to all users of the UPD Main Library.
It is also recommended that INVITE be presented during the Freshmen Orientation Program and be the foremost promoter of the UPD University Library. INVITE could be a significant addition to the UP student's arsenal to maximize their potentials for the betterment of the nation and the academe.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman Main Library; Library orientation -- Philippines -- Quezon City; Computer software